Analysis of the relationship between environmental policies and air quality during major social events. Issue 3 (2nd July 2016) - Zhang, Ruiliang; Shi, Guoqing
ABSTRACT: Based on an analysis of major recent social events in China, such as the 2008 Beijing Olympic Games, 2010 Shanghai World Expo, 2014 Nanjing Youth Olympic Games, and 2014 Beijing Asia Pacific Economic Cooperation Conference, mandatory, temporary, and indemnificatory quantitative policies aimed at protecting air quality, which were carried out by both central and local governments, made substantial contributions to changes and improvements in air quality. To some extent, the findings show that command and control measures play a significant role in protecting air quality, while the law and economic and voluntary environmental safeguard measures do not during major social events. Therefore, it reminds us the air quality could and will improve not only during major social events but also in the regular days if we implement appropriate environmental policies and safeguard measures.